Utilização de fosfato monoamônico e resíduos de poda de árvores para produção de composto - Grassi, Fernando Daniel (2014)
This study had the objective to evaluate two residues, being one the trees prune residues and the other chemical powder of monoamonico phosphate and ammonium sulfate, used in fire extinguisher ABC class. It was used composting techniques with five different proportions of residues, using trees prune proportions and chemical powder to the treatment 1, 2, 3, 4 and 5 of 55/45, 65/35, 75/25, 85/15 and 95%, it characterized the residues in C/N relation to define the proportions to each treatment, and by monitoring the treatments as for the moisture rates, temperature and pH in a period of 120 days, to the control of the process. On the basis of parameters of the analyzed nourishments, it concluded that the best result taken among the treatments was the treatment that started with C/N relation of 40/1 and achieved the end of the composting process with 9,4/1 relation in the proportions 95% of trees prune and 5% of chemical powder, pH 5,95 and approximately 59% humidity.